2015
DOI: 10.1155/2015/690916
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing versus Destabilizing the Microtubules: A Double-Edge Sword for an Effective Cancer Treatment Option?

Abstract: Microtubules are dynamic and structural cellular components involved in several cell functions, including cell shape, motility, and intracellular trafficking. In proliferating cells, they are essential components in the division process through the formation of the mitotic spindle. As a result of these functions, tubulin and microtubules are targets for anticancer agents. Microtubule-targeting agents can be divided into two groups: microtubule-stabilizing, and microtubule-destabilizing agents. The former bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 189 publications
2
62
0
1
Order By: Relevance
“…We showed that PPP2R5E is required for the stabilization of MTCL1. Disruption of MT organization is associated with a loss of cell polarity and a defect in cell division, which are often observed in malignant cancer cells . Our results suggest the possibility that MT organization induced by the stabilization of MTCL1 may be one of the mechanisms for PPP2R5E‐mediated tumor suppression.…”
Section: Discussionmentioning
confidence: 58%
“…We showed that PPP2R5E is required for the stabilization of MTCL1. Disruption of MT organization is associated with a loss of cell polarity and a defect in cell division, which are often observed in malignant cancer cells . Our results suggest the possibility that MT organization induced by the stabilization of MTCL1 may be one of the mechanisms for PPP2R5E‐mediated tumor suppression.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, microtubule-destabilizing agents suppress tubulin polymerization and can be further characterized into two groups: vinca-domain binders and colchicine-domain binders. Although the wide application of microtubule inhibitors is observed, there is urgent need to overcome several emerging challenges including drug-resistance and neurotoxicity [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Most microtubule targeting drugs (stabilizing or destabilizing) exploit this delicate moment of mitotic cell division to exert their cytotoxic activity, often by the common mechanism of suppressing microtubule dynamics and the chronic activation of spindle assembly checkpoint-SAC which halts cell-division in a prolong event that signals the induction of apoptosis (figure 1) [9]. Anti-mitotics like the vinca alkaloids (vinflunine, vincristine, vinorelbine, vindesine and eribulin), cryptophycins, halichondrins, estramustine, colchicines, and combretastatins are examples of drugs known to depolymerize / destabilize microtubules by binding to various β-tubulin sites [5,10,11]. On the other hand, taxanes paclitaxel (Taxol), Laulimalide, Dictyostatin, the epothilones, etc.…”
Section: Introductionmentioning
confidence: 99%